Preferensi Masyarakat dalam Penyaluran Zakat: Tinjauan pada Masyarakat di Kabupaten Banjar - Ainun, Basyirah; Mahyuni; Silvia, Nifa (P3M Politeknik Negeri Banjarmasin, 2023)
Zakat is a number of assets that must be issued by a Muslim or business entity to be given to those who are entitled to receive it in accordance with Islamic law. Banjar Regency is known as one of the districts in South Kalimantan whose community is predominantly Muslim and very religious so it should be able to optimize its zakat collection potential. This study aims to determine the preferences of people in Banjar Regency in distributing zakat funds and what factors influence it. The research method used was descriptive qualitative with primary data in the form of survey to 100 respondents. The results showed that as many as 60% of respondents preferred to distribute zakat directly to mustahiq because of their lack of knowledge about zakat management organizations, while 40% of respondents chose to distribute zakat through zakat management organizations with details of 30% choosing to distribute zakat through government-formed zakat collection organizations (BAZNAS) and 10% choosing to distribute zakat through community-formed zakat management organizations such as LAZISMU, Rumah Zakat, Dompet Dhuafa, and BSI Maslahat. Several factors affect public trust in zakat management organizations including openness, competent management, honesty, integrity, accountability, and respect for others